Levels of agreement for RR intervals and short-term heart rate variability obtained from the Polar S810 and an alternative system - Nunan, D.; Jakovljevic, D. G.; Donovan, G.; Hodges, L. D.; Sandercock, G. R. H.; Brodie, D. A. (European Journal of Applied Physiology, 2008)
The aim of this study was to assess the agreement between HRV measures derived from a time series of RR intervals recorded by a standard 12-lead ECG (CP) and a commercially available RR interval recorder (S810). Thirty-three participants (19 males) (median age 36, range 20-63) underwent simultaneous, 5-min, supine RR-interval recordings. Each RR interval time series was analysed using the software supplied with the recording equipment. Two comparisons were then made. First, a comparison of RR interval data recording and editing only was made. Second, comparisons were made for measures of HRV derived from edited RR interval data. Agreement between RR intervals and standard HRV measures were assessed using intraclass correlation coefficient and limits of agreement. Agreement of HRV measures derived from RR intervals recorded and edited by individual systems was not acceptable. Agreement analyses for the number of RR intervals recorded and edited by each systems software showed excellent intraclass correlation coefficients (ICC lower 95% CI > 0.75) and acceptably narrow limits of agreement (LoA). These data indicate that the number of RR intervals recorded by S810 can agree well those recorded from a standard 12-lead ECG. This is true even after application of system specific data editing procedures. Commercial RR-interval recorders may offer a simple, inexpensive alternative to full 12-lead ECG in the recording and editing of RR intervals for subsequent HRV analysis in healthy populations.